MEMBUMIHANGUSKAN MOJOAGUNG: KONDISI MOJOAGUNG 1945-1949 - Santoso, Alfian Widi (Historia Islamica: Journal of Islamic History and Civilization, 2022)
Mojoagung is a sub-district located on the eastern outskirts of Jombang district which is also directly adjacent to Mojokerto district. Mojoagung itself has a very long history, because Mojoagung itself is a very strategic area, because it is crossed by roads between provinces. With its strategic position, Mojoagung eventually occupied several historical stages from the Islamic Mataram period to the post-independence period. Therefore, this writing aims to discuss something that is quite interesting and very related to today, namely "Membumihanguskan Mojoagung: Kondisi Mojoagung 1945-1949”. This discussion has the purpose of analyzing the situation and condition of Mojoagung and the buildings during the Physical Revolution which was known as the total scorched earth action that was carried out. In this study has a temporal limit with a range of years 1945-1949. The method used in this paper is historical methodology in general as proposed by Kuntowijoyo which includes five stages, namely topic selection, heuristics (collection of sources can be in the form of written or oral), verification (internal and external criticism of sources), interpretation (analytic interpretation and synthesis), and historiography (writing history). The results of this study are to show the destruction that occurred until there was no trace, and the impact on the disconnection of the memory of Mojoagung in the past.